Penegakan Hukum Terhadap Pelaku Kekerasan Seksual Kepada Korban Dalam Praktik Penerapan Hukum Pidana - Br. Sembiring, Mila Sari; Ogestina Tampubolon, Salendion; Siagian, Nurhayati; Hutahaean, Hendra; Yunita, Sri (GEMA EKONOMI, 2023)
The Act Number 35 of 2014, violence is any act against children that results in physical, psychological, sexual, and/or neglectful misery or suffering, including threats to commit unlawful acts, coercion, or deprivation of independence. Sexual violence is defined as any sexual act, attempt to perform a sexual act, comment or suggest to involuntary sexual behavior or vice versa, an act of violation to have sexual intercourse by force on someone. (WHO, 2017). Sexual assault is an issue that has long been a topic of discussion in Indonesian society. In Indonesia itself, the word sexual harassment is familiar because almost every year cases of sexual harassment occur. The problem of sexual violence has often been heard in the ears of the Indonesian people. However, Indonesian law has not fully provided strict legal consequences for perpetrators and protection for victims, Therefore, the purpose of writing this research is to find out what law enforcement is like against perpetrators of sexual violence and how legal protection is for victims. This study uses a normative legal research method which is part of the typology of doctrinal research. The research approach used statutory approach and a conceptual approach. The results of this study indicate that the draft criminal law for cases of sexual violence is an urgent matter, given the rise of cases of sexual violence in Indonesia. The making laws that protect victims of sexual violence, the resolution of cases of sexual violence and protection of victims of cases of sexual violence can be carried out properly